Generation, Gender, and Leadership: Metaphors and Images - Burkinshaw, Paula; White, Kate (Frontiers in Education, 2020)
This article explores the metaphors and images used by different generations of women to describe women's leadership in higher education (HE) and the impact these perceptions have on their careers and career ambitions. It also explores how such metaphors and images can position them as “other,” silence their voices in the dominant masculinist discourse, and marginalize them. The emphasis in the gender and higher education literature has been on identifying the barriers that impede women's progress in academic organizations, including images of continuing hegemonic masculine leadership, and their promotion to leadership positions. These models position women leaders who are assertive as troublemakers, and women as “the problem” either because of their attitudes or perceived domestic and family responsibilities. And while women leaders are often not gender conscious, they are frequently doing gender in their senior roles. The metaphors and images that portray women's leadership are often of hidden work, supporting more senior males, or “ivory basement” leadership. Combined, they suggest a deficit model that positions women as lacking for top jobs, and institutions therefore needing to “fix the women” generally through leadership development programmes, sponsorship and mentoring. The article examines the metaphors and images used to describe women's leadership across two generations. Older women often saw their leadership as conforming to male leadership models, as fitting in, and not challenging or unsettling their male colleagues. However, a younger generation of leaders or prospective leaders had a very different set of metaphors for their leadership. They saw themselves as unsupported by what they described as the current mediocre, institutional leaders, weighed down by inexorable organizational restructure, and merely in survival mode. Hence, they refused to accept the masculinist leadership model which they perceived as ineffectual, outdated and not meeting their needs. The article suggests that the prevailing culture in higher education leadership and the metaphors and images used to describe successful leadership narrows the options for women leaders. While older women were prepared to accept current masculinist leadership, younger women had contempt for the way it marginalized them while at the same time encouraging them to lift their game and had a different set of metaphors and images to portray what successful leadership should look like.